Engineering Corynebacterium glutamicum for synthesis of poly(3‐hydroxybutyrate) from lignocellulose biomass. Issue 6 (3rd March 2022) - Jin, Ci; Li, Jing; Huang, Zhen; Han, Xushen; Bao, Jie
Abstract: Lignocellulose is the only feasible carbohydrates feedstock for commercial scale and carbon neutral production of poly(3‐hydroxybutyrate) (PHB) biopolymer by its great abundance and availability. Microbial cell factories for fermentative PHB synthesis are highly restricted by the growth suppression of inhibitors from lignocellulose pretreatment. This study targeted a potential PHB‐producing cell factory Corynebacterium glutamicum owing to its strong inhibitors tolerance. A systematic metabolic engineering was conducted starting with the stable PHB synthesis pathway construction from glucose and xylose, followed by the enhancement of PHB synthesis on PHA synthase activity and stability, cell morphology modification, and growth factors regulation. The relocation of the PHA synthase on the cell membrane guided by secrete signal peptides and cell membrane display motifs increased the PHB content by 2.4 folds. Excessive nitrogen preferentially promoted the PHB synthesis capacity and resulted in the PHB content increased by 13.3 folds. Modification of the genes responsible for cell division changed the cell morphology but the cell size was not enlarged to a PHB accumulation favorable environment. The metabolic engineering of C. glutamicum resulted in a high fermentative production of PHB using wheat straw as feedstock. This study provided an important microbial cell factory choice for PHB production using lignocellulose feedstock. Abstract : The strong inhibitors tolerant Corynebacterium glutamicum was engineered with poly(3‐hydroxybutyrate) (PHB) synthesis and xylose assimilation pathways integrated in the genome scale. Membrane‐located expression of PHA synthase and excessive nitrogen stress enhanced the PHB synthesis. The engineered C. glutamicum results in highly improved PHB production using wheat straw feedstock.